English newspapers as sources of Malaysian history - Khoo, K.K. (University of Malaya Library, 1985)
Explores the role of English newspapers in recording events of its time and therefore are important source of reference and research for historians. The first Enlish newspaper was published in Penang in 1805, followed by others. This resource have not been fully uilized in Malaysia. Although the old newspapers initially reported mainly on the society in Europe, economcs and commerce, their orientation gradually changed to include social-cultural issues of the Malays, Chinese and Indians in Malaysia. A large proportion of the newspapers described are available at the University of Malaya Library in the form of microfilms.